Peran Guru Sebagai Teladan Dalam Upaya Pembentukan Karakter Siswa Berdasarkan Kajian Filsafat Aksiologi Kristen - Helen Melenia Sianipar; Wahyu Irawati (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Character is a basic thing that must be owned by students as the basis for ways of thinking and behaving and reflecting their identity. However, the facts show that many students experience a character crisis. This is shown through bullying and undisciplined and irresponsible attitudes that show that it is very important to build student character. Based on the philosophy of Christian axiology, ethics has an important role in the process of building students' characters who are more like Christ. Students as representatives of God are expected to have good character according to the values of truth and reflect the character of Christ. However, they fall into sin has caused humans to tend to take actions that are contrary to the values of truth. This also happens to students who are shown through acts of bullying, stealing, cheating, and other negative things. The purpose of this paper is to examine the role of the teacher as a role model to build student character based on a review of Christian axiological philosophy by using the literature review method. The results obtained indicate that the role of Christian teachers as role models is very important in efforts to build student character. Christian teachers who have been born again and are led by the Holy Spirit will be enabled to understand axiological values based on Bible truth so that they can provide concrete examples to shape students' character in the form of exemplary attitudes and actions. It is recommended for further research to examine and analyze more deeply the role of the teacher as a role model in the building of student character.